Management of childhood acute diarrhea with Probiotics in Ambulatory Care (MIRACLE) - AGHA SHABBIR ALI; ZEESHAN HASSAN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Probiotics are widely regarded as effective in the management of acute diarrhea. Aim: To document usage of probiotics in children presenting with acute diarrhea at outpatient clinics across Pakistan, while also evaluating caregiver satisfaction with various aspects of their use. Methods: This national, observational, multicentre study was conducted in outpatient settings as a non-interventional analysis of therapeutic practices. A prospective design with a single follow-up was used and general practitioners and paediatricians were randomly selected to participate. The study included children aged ≥1 month to under ≤5 years who presented with acute diarrhea in ambulatory care. Results: Of the 1,130 children enrolled at the initial visit, 1,072 returned for follow-up. Probiotics were prescribed to 98.6% of these children. The most commonly recommended probiotics were Bacillus clausii (73%), followed by Saccharomyces boulardii (17%) and Lactobacillus species (6%). Caregiver satisfaction was high, with 94.3% (n=1,011) expressing approval of the prescribed treatment. Physicians observed that probiotics were primarily effective in reducing the loose consistency of stools. Practical Implication: The use of ORS is widespread though not universal and should be further promoted. Probiotic use is widely prevalent. However, there is the room for increasing awareness on usage of probiotics both at primary health care level and at caregiver level. In this study the prescribed probiotics reduced diarrheal symptoms within 3.3 days and improved stool consistency in more than 86% of the cases. Conclusion The exact proportion of probiotic prescriptions alongside other antidiarrheal treatments for children with acute diarrhea remains unclear. However, findings from this registry highlight that a significant rate of probiotic prescriptions is closely linked to high caregiver satisfaction with the treatment. The MIRACLE study represents an important step toward fostering awareness and building confidence in the use of probiotics for managing acute diarrhea in the general paediatric population of Pakistan. Keywords: Acute diarrhea, Probiotics, Modified Vesikari Score, Bacillus clausii, caregiver Satisfaction